PENGARUH STRATEGI CO-BRANDING TERHADAP KEPUTUSAN PEMBELIAN - Lina Budiarti; Rena Feri Wijayanti (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2023)
Co-branding is often striven by marketers. There are many advantages of co-branding for a brand that makes many companies do joint branding. This research was conducted with the aim of knowing the effect of co-branding strategy on purchasing decisions. Consumers who use the co-branding product Dear Me Beauty with KFC were chosen as the population of this study, with a sample of 62 people selected by purposive sampling technique. The hypothesis was tested using simple linear regression analysis which resulted in the finding that co-branding had an effect on purchasing decisions.